Colorimetric detection of SARS‐CoV‐2 variants with paper‐based analytical devices. Issue 1 (18th March 2023) - Wang, Qi; Chen, Zhaowei; Yang, Huanghao
Abstract : Given that the severe acute respiratory syndrome coronavirus 2 (SRAS‐CoV‐2) virus keeps mutating during the COVID‐19 pandemic, there is an urgent need to develop a quick and convenient test method to detect real‐life samples for mass on‐site screening. Zhang et al. proposed a novel strategy for rapid detection and discrimination of SARS‐CoV‐2 and its variants at rather low cost utilizing a subtly designed DNA probe. By combining with a paper‐based colorimetric amplification platform, the results could be analyzed by the naked eyes or a widely used smartphone.